Probiotic Properties of Bacillus proteolyticus Isolated From Tibetan Yaks, China - Zeng, Zhibo; He, Xiaoling; Li, Feiran; Zhang, Yan; Huang, Zonghao; Wang, Yaping; Li, Kun; Bao, Yuhua; Iqbal, Mudassar; Fakhar-e-Alam Kulyar, Muhammad; Li, Jiakui (Frontiers in Microbiology, 2021)
Yaks (Bos grunniens) that live primarily in high-altitude hypoxic conditions have a unique intestinal micro-ecosystem, remarkable flexibility, and strong resistance. Accumulating evidence revealed the importance of probiotics in host metabolism, gut microbiota, growth performance, and health. The goal of this study was to screen out probiotics with excellent probiotic potential for clinical application because research on yak-derived probiotics is still limited. In our study, four strains of Bacillus, i.e. Bacillus proteolyticus (named Z1 and Z2), Bacillus amyloliquefaciens (named J), and Bacillus subtilis (named K), were isolated and identified. Afterwards, their probiotic potential was also subsequently evaluated. Antioxidant activity tests revealed that Z1 had the highest DPPH and hydroxyl radical scavenging activity, whereas Z2 had higher reducing power and inhibited lipid peroxidation. Additionally, the antibacterial testing revealed that all strains were antagonistic to three indicator pathogens, Escherichia coli C83902, Staphylococcus aureus BNCC186335 and Salmonella enteritidis NTNC13349. These isolates also had a higher hydrophobicity, auto aggregation, acid and bile tolerance, all of which helped to survive and keep dangerous bacteria out of the host intestine. Importantly, all strains could be considered safe in terms of antibiotic susceptibility and lack of hemolysis. In conclusion, this is the first study to show that Bacillus proteolyticus and Bacillus amyloliquefaciens isolated from yaks have probiotic potential, providing a better foundation for future clinical use.